(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
The oil quench and temper technique have a lot of benefits for heavy duty spring manufacture since it may expose the best balance of toughness and ductility, as well as increase fatigue life. The current study looked at the fatigue behavior of tempered AISI 5160 leaf spring steel samples at tempering temperatures of 400, 450, 500, 550, and 600 °C, as well as isothermally heat- treated steel samples at 830 °C. All leaf spring steel samples that had undergone thermal tempering and isothermal heat treatment were then tested up to fracture utilizing rotational fatigue test equipment under the effect of various stress levels. All steel samples subjected to tempering heat treatments of 400°C to 600°C showed a decrease in hardness ratings. The Rockwell hardness ratings of the steel samples that treated to isothermal heat treatment increased significantly. Experimental fatigue testing revealed that the values of fatigue resistance for steel samples tempered at (400 and 450) °C temperatures dropped by a small amount. The fatigue resistance values for steel specimens tempered at 500 °C to 600 °C temperatures decreased more than the values for steel samples tempered at 500 to 600 °C temperatures. A fatigue resistance of steel samples that were treated to isothermal heat treatments, on the other hand, increased. Steel samples that were isothermally heat-treated at 830 °C and then chilled in a salt brine solution, on the other hand, showed an increase in fatigue resistance